Virgil, Aeneid 5 : text, translation and commentary - Virgil. (Mnemosyne, Supplements, 2015)
Virgil's Aeneid 5 has long been among the more neglected sections of the poet's epic of Augustan Rome. Book 5 opens the second movement of the poem, the middle section of the Aeneid that sees the Trojans poised between the old world of Phrygia and the new destiny in Italy. The present volume fills a significant gap in Virgilian studies by offering the first full-scale commentary in any language on this key book in the explication of the poet's grand consideration of the meaning of Trojan versus Roman identity. A new critical text (based on first hand examination of the manuscripts) is accompanied by a prose translation and detailed commentary. The notes provide in depth analysis of literary, historical, and lexical matters; the introduction situates Book 5 both in the context of the epic and the larger tradition of heroic poetry.